Composite adaptive control for bilateral teleoperation systems without persistency of excitation. Issue 2 (January 2020) - Li, Yuling; Yin, Yixin; Zhang, Sen; Dong, Jie; Johansson, Rolf
Abstract: Composite adaptive control schemes, which use both the system tracking error and the prediction error to drive the updating law, have become widespread in achieving an improvement of system performance. However, a strong persistent-excitation (PE) condition is required to guarantee the convergence of the parameter estimation errors. This paper proposes a novel composite adaptive control for nonlinear teleoperation systems with dynamic uncertainties and time-varying communication delays, by which the parameter convergence is achieved without the PE condition. The novelty lies in the construction of the prediction errors by designing lower-bounded gain matrices of the prediction errors. The stability criteria of the closed-loop teleoperation system are given in terms of linear matrix inequalities. Simulation studies are given to show the effectiveness of the proposed method.